Emotions delay care-seeking in patients with an acute myocardial infarction. (February 2014) - Nymark, Carolin; Mattiasson, Anne-Cathrine; Henriksson, Peter; Kiessling, Anna
Background: In acute myocardial infarction the risk of death and loss of myocardial tissue is at its highest during the first few hours. However, the process from symptom onset to the decision to seek medical care can take time. To comprehend patients' pre-hospital delay, attention must be focused on the circumstances preceding the decision to seek medical care. Aim: To add a deeper understanding of patients' thoughts, feelings and actions that preceded the decision to seek medical care when afflicted by an acute myocardial infarction. Methods: Fourteen men and women with a first or second acute myocardial infarction were interviewed individually in semi-structured interviews. Data were analysed by qualitative content analysis. Results: Four themes were conceptualized: 'being incapacitated by fear, anguish and powerlessness', 'being ashamed of oneself', 'fear of losing a healthy identity' and 'striving to avoid fear by not interacting with others'. Patients were torn between feelings such as anguish, fear, shame and powerlessness. They made an effort to uphold their self-image as being a healthy person thus affected by an unrecognized discomfort. This combined with a struggle to protect others from involvement, strengthened the barriers to seeking care. Conclusions: The present study indicates that emotional reactions are important and influence patients' pre-hospital behaviour. Being ashamed of oneself stood out as a novel finding. Emotions might be an important explanation of undesired and persisting patient delays. However, our findings have to and should be evaluated quantitatively. Such a study is in progress.